Relation Between Left Atrial Wall Thickness in Patients with Atrial Fibrillation and Intracardiac Electrogram Characteristics and ATP‐Provoked Dormant Pulmonary Vein Conduction. (1st May 2015) - TAKAHASHI, KEIKO; OKUMURA, YASUO; WATANABE, ICHIRO; NAGASHIMA, KOICHI; SONODA, KAZUMASA; SASAKI, NAOKO; KOGAWA, RIKITAKE; ISO, KAZUKI; OHKUBO, KIMIE; NAKAI, TOSHIKO; HIRAYAMA, ATSUSHI
LA Wall Thickness, LA Electrogram, and Dormant PV Conduction Introduction Atrial remodeling plays a key role in development of the substrate for atrial fibrillation (AF). Whether the wall thicknesses of the left atrium (LA) and pulmonary vein (PV)–LA junction affect remodeling and AF ablation is unknown. We investigated the relationship between wall thicknesses, electrogram characteristics, and adenosine triphosphate (ATP)‐provoked dormant PV conduction as they pertain to AF. Methods In 50 patients with AF and 25 patients without AF, wall thicknesses of the LA and PV–LA junction were measured on 320‐slice computed tomography images. For the AF patients, NavX‐based voltage maps generated during sinus rhythm were obtained, and ATP‐provoked dormant PV conduction after PV isolation was evaluated. Results Walls of the LA and PV–LA junction were significantly thicker in the AF patients than in the control patients (1.83 ± 0.29 mm vs. 1.59 ± 0.28 mm, respectively; P = 0.0010; and 0.88 ± 0.14 mm vs. 0.65 ± 0.11 mm, P<0.0001, respectively). Wall thickness at the PV–LA junction was independently associated with AF (β = 0.40, P = 0.0002). In AF patients, the walls of the PV–LA junction showed stepwise thickening across bipolar voltages indicative of severe (bipolar voltage <33rd percentile) to moderate (33rd–66th percentiles) to mild fibrosis/scarring (≥66th percentile). Walls of the PV–LA junction with dormant PV conduction were significantly thicker than those without it (0.94 ± 0.19 mm vs. 0.86 ± 0.21 mm, respectively; P = 0.0025). Conclusions Together, the association between thickened PV–LA junction walls and AF and the increased bipolar voltage suggests that such wall thickening increases PV electrical activities, leading to initiation and maintenance of AF and perhaps to ATP‐provoked dormant PV conduction.